2022
DOI: 10.47897/bilmes.1132562
|View full text |Cite
|
Sign up to set email alerts
|

Anomaly Diagnosis Using Autoencoder in Edge Computing Systems

Abstract: IoT sistemleri geleneksel buluta bağlı bir mimaride çalışır. IoT cihazlarında oluşturulan veriler buluta aktarılır, orada depolanır ve daha sonra anlamlı bilgiler çıkarmaya çalışarak işlenir. Ancak tercih edilen bu yapıda sürekli buluta bağımlı olmanın dezavantajları oldukça yüksektir. Her bir bilgi parçasının ham olarak buluta aktarılması ağ trafiğini artırırken, verileri yalnızca bulut katmanında işlemek için yüksek donanım gücü gerektirir. UBISOKKAT (Edge Computing Systems Kullanarak Otomatik Kodlayıcı Kul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In order to mitigate the frequent use of identical Packet Forwarding Nodes (PFNs), the movement of packets is postponed. During the commencement of packet transmission, the criteria being established are security and energy usage [4][5][6]. In the context of Wireless Sensor Networks (WSN), it has been observed that the initial energy level of the Sensor Node (SP) is four times greater than the energy level of the SP involved in data transmission within the network [7].…”
Section: Introductionmentioning
confidence: 99%
“…In order to mitigate the frequent use of identical Packet Forwarding Nodes (PFNs), the movement of packets is postponed. During the commencement of packet transmission, the criteria being established are security and energy usage [4][5][6]. In the context of Wireless Sensor Networks (WSN), it has been observed that the initial energy level of the Sensor Node (SP) is four times greater than the energy level of the SP involved in data transmission within the network [7].…”
Section: Introductionmentioning
confidence: 99%